The Evolutionary Pattern and the Regulation of Stearoyl-CoA Desaturase Genes. (7th November 2013) - Wu, Xiaoyun; Zou, Xiaoju; Chang, Qing; Zhang, Yuru; Li, Yunhai; Zhang, Linqiang; Huang, Jingfei; Liang, Bin
Abstract : Stearoyl-CoA desaturase (SCD) is a key enzyme that converts saturated fatty acids (SFAs) to monounsaturated fatty acids (MUFAs) in the biosynthesis of fat. To date, two isoforms of scd gene ( scd1 and scd5 ) have been found widely existent in most of the vertebrate animals. However, the evolutionary patterns of both isofoms and the function of scd5 are poorly understandable. Herein, we aim to characterize the evolutionary pattern of scd genes and further predict the function differentiation of scd genes. The sequences of scd genes were highly conserved among eukaryote. Phylogenetic analysis identified two duplications of scd gene early in vertebrate evolution. The relative rate ratio test, branch-specific dN/dS ratio tests, and branch-site dN/dS ratio tests all suggested that the scd genes were evolved at a similar rate. The evolution of scd genes among eukaryote was under strictly purifying selection though several sites in scd1 and scd5 were undergone a relaxed selection pressure. The variable binding sites by transcriptional factors at the 5′-UTR and by miRNAs at 3′-UTR of scd genes suggested that the regulators of scd5 may be different from that of scd1 . This study promotes our understanding of the evolutionary patterns and function of SCD genes in eukaryote.